Plasma microRNAs as biomarkers of pancreatic cancer risk in a prospective cohort study. Issue 5 (12th June 2017) - Duell, Eric J.; Lujan‐Barroso, Leila; Sala, Núria; Deitz McElyea, Samantha; Overvad, Kim; Tjonneland, Anne; Olsen, Anja; Weiderpass, Elisabete; Busund, Lill‐Tove; Moi, Line; Muller, David; Vineis, Paolo; et al.
Abstract : Noninvasive biomarkers for early pancreatic ductal adenocarcinoma (PDAC) diagnosis and disease risk stratification are greatly needed. We conducted a nested case‐control study within the Prospective Investigation into Cancer and Nutrition (EPIC) cohort to evaluate prediagnostic microRNAs (miRs) as biomarkers of subsequent PDAC risk. A panel of eight miRs (miR‐10a, ‐10b, ‐21‐3p, ‐21‐5p, ‐30c, ‐106b, ‐155 and ‐212) based on previous evidence from our group was evaluated in 225 microscopically confirmed PDAC cases and 225 controls matched on center, sex, fasting status and age/date/time of blood collection. MiR levels in prediagnostic plasma samples were determined by quantitative RT‐PCR. Logistic regression was used to model levels and PDAC risk, adjusting for covariates and to estimate area under the receiver operating characteristic curves (AUC). Plasma miR‐10b, ‐21‐5p, ‐30c and ‐106b levels were significantly higher in cases diagnosed within 2 years of blood collection compared to matched controls (all p ‐values <0.04). Based on adjusted logistic regression models, levels for six miRs (miR‐10a, ‐10b, ‐21‐5p, ‐30c, ‐155 and ‐212) overall, and for four miRs (‐10a, ‐10b, ‐21‐5p and ‐30c) at shorter follow‐up time between blood collection and diagnosis (≤5 yr, ≤2 yr), were statistically significantly associated with risk. A score based on the panel showed a linear dose‐response trend with risk ( p ‐value = 0.0006). For shorter follow‐up (≤5 yr), AUC for the score was 0.73, and for individual miRs ranged from 0.73 (miR‐212) to 0.79 (miR‐21‐5p). Abstract : What's new? Pancreatic cancer has the worst prognosis of all cancers because of late detection, and early noninvasive biomarkers are urgently needed to improve outcome. Here, the authors examined blood levels of a panel of microRNAs previously associated with pancreatic cancer. Samples collected within two years of a cancer diagnosis showed elevated plasma levels of miR‐10b, miR‐21‐5p, miR‐30c and miR‐106b. In multivariable models, three of these microRNAs (10b, 21‐5p, 30c) as well as miR‐10a showed significant associations with subsequent risk underscoring the clinical potential of plasma microRNAs in pancreatic cancer screening.